2019
DOI: 10.3390/su11154213
|View full text |Cite
|
Sign up to set email alerts
|

Biowaste Management in Italy: Challenges and Perspectives

Abstract: The aim of this work is the development of a methodology for the technical and environmental assessment of biowaste valorization in 2G biorefineries. Italy was chosen as case study, considering years 2016–2017. Approach: the Italian context was evaluated through the following key parameters: Gross domestic power, climate, demography, and population density distribution described the Italian framework. The four most abundant biowaste categories were defined through their amounts and geo-localization: wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Biomass is considered the best option for renewable and suitable energy that can replace a large portion of fossil fuels, besides solar and wind energy. Meanwhile, bioenergy will contribute to enhance developed countries' standard of life, as it is a potent source for biofuels [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass is considered the best option for renewable and suitable energy that can replace a large portion of fossil fuels, besides solar and wind energy. Meanwhile, bioenergy will contribute to enhance developed countries' standard of life, as it is a potent source for biofuels [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other works indicate biowaste processing in AD installations has a positive effect on the reduction of Greenhouse Gases emissions [39]. For example, in their paper, Demichelis et al concluded that for the case study of Italy biowaste treatment, avoided CO 2 emissions were increased between 10% and 89.9%, when applying AD instead thermal treatment [40]. The work of Zeller et al, analysing circular biowaste management options at city-region level, concludes that AD treatment combined with separate collection may be beneficial in terms of meeting environmental criteria (based on life cycle assessment) [41].…”
mentioning
confidence: 99%
“…Agricultural waste is defined as the residue from the growing and processing of raw agricultural products such as fruits, vegetables, poultry, and livestock [59]. However, agricultural activities depend on the geo-localization of the region as well as the activities of its citizens.…”
Section: Biowaste Generated By the Agricultural Sectormentioning
confidence: 99%
“…The substantial flows generated by the livestock and poultry sectors in Nebeul are due to the enhancement of agro-activities from traditional animal breeding, mainly for personal consumption or local market distribution to an active industrial production. Agricultural waste is defined as the residue from the growing and processing of raw agricultural products such as fruits, vegetables, poultry, and livestock [59]. However, agricultural activities depend on the geo-localization of the region as well as the activities of its citizens.…”
Section: Biowaste Generated By the Agricultural Sectormentioning
confidence: 99%